Pengaruh Desain Produk Terhadap Keputusan Pembelian Pada PM Collection Pekanbaru - Novi Suci Ramadhani; Annisa Mardatillah (Pelantar Press, 2024)
Product design is the design of an object so that it has added value in various aspects such as more effective function, more beautiful appearance, easier and more comfortable use and is not difficult to maintain so that it can then be re-produced industrially more efficiently, both economically and technically so as to provide benefits for consumers (customers) and producers. One product that requires good design is the PM Collection Pekanbaru. This research aims to determine and analyze product design on purchasing decisions at PM Collection Pekanbaru. The indicators of product design used are shape, style, quality, features, durability, reliability,and repairability. This research is located at the PM Collection Pekanbaru using a descriptive research type that prioritizes questionnaires as a data collection tool and the empirical conditions of the research location. The method used is quantitative. The population in this study were PM Collection Pekanbaru customers. The sample of this research was 100 people. The sampling technique used was accidental sampling. The type and technique of data collection used consists of primary data collected by observation, questionnaires and interviews. Based on the results, the data analysis technique used is descriptive analysis. Based on this analysis technique, the researcher assessed and concluded that product design has a significant influence on purchasing decisions at PM Collection Pekanbaru.Â Â